2014
DOI: 10.1071/an13033
|View full text |Cite
|
Sign up to set email alerts
|

The impact of best practice health and husbandry interventions on smallholder cattle productivity in southern Cambodia

Abstract: Future food security has become a major global concern and is particularly important in the Greater Mekong Subregion where several countries have seen rapid urban economic development and increasing demand for red meat. In Cambodia, the majority of livestock producers are subsistence or semi-subsistence rural smallholder farmers using cattle as a source of protein, fertiliser, draught power, and asset storage. Potential income from smallholder cattle is limited by a range of factors that compromise productivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 12 publications
(25 reference statements)
0
44
0
Order By: Relevance
“…The average daily gain (kilograms) as used in a similar study (Young et al., ) was included and represents the low growth rate achieved in traditional smallholder systems. However, variations in live weight gain by different age groups, seasonal impacts on feed availability and quality and environmental stress such as heat were not accounted for in this study (Young et al., ,b). It was assumed that ‘all’ smallholder farmers with secondary employment will lose 1 day of employment (‘returns foregone’) and that all farmers will rent 1 day of alternative draught per vaccination (‘extra cost’).…”
Section: Discussionmentioning
confidence: 91%
“…The average daily gain (kilograms) as used in a similar study (Young et al., ) was included and represents the low growth rate achieved in traditional smallholder systems. However, variations in live weight gain by different age groups, seasonal impacts on feed availability and quality and environmental stress such as heat were not accounted for in this study (Young et al., ,b). It was assumed that ‘all’ smallholder farmers with secondary employment will lose 1 day of employment (‘returns foregone’) and that all farmers will rent 1 day of alternative draught per vaccination (‘extra cost’).…”
Section: Discussionmentioning
confidence: 91%
“…It is widely recognized that livestock movement is probably the single most important method of transmission of FMD virus in those countries where FMD is endemic (Rosenberg et al., ; Rweyemamu, ; Fonnan, ; Ferris et al., ; Windsor, ). Recent research has indicated that smallholder farmers within villages sell 17% of cattle per annum; however, this is considered to be an underestimation (Young et al., ). Considering that 85% of smallholders own three or fewer cattle (Young et al., ), this high annual sale rate, combined with other mobility uses (draught and transport) and communal grazing, would likely provide multiple opportunities for direct contact and opportunity for disease transmission.…”
Section: The Need For Improved Biosecuritymentioning
confidence: 99%
“…Recent research has indicated that smallholder farmers within villages sell 17% of cattle per annum; however, this is considered to be an underestimation (Young et al., ). Considering that 85% of smallholders own three or fewer cattle (Young et al., ), this high annual sale rate, combined with other mobility uses (draught and transport) and communal grazing, would likely provide multiple opportunities for direct contact and opportunity for disease transmission. Cleland et al.…”
Section: The Need For Improved Biosecuritymentioning
confidence: 99%
“…While rice production remains the major contributor to the agricultural sector, livestock play an important role in smallholder farm systems. Livestock often serve multiple purposes including a source of draught power for transport and tillage, manure for biodigester fuel and fertilizer, sale for beef, and importantly as a cash asset store which can be sold when money is needed (Shankar et al., ; Young et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the national large ruminant herd declined 3.1% between 2009 and 2010 and a further 2.0% between 2010 and 2011 (Suon et al., ). In 2011, the national herd comprised 3 406 972 cattle and 692 611 buffalo with over 99% of large ruminants owned by smallholder farmers, typically owning 3 or fewer animals (Young et al., ). Production levels are low, with mean average daily weight gains of ~50 g per day, poor body condition year round and poor reproductive performance (Young et al., ).…”
Section: Introductionmentioning
confidence: 99%